Acute Reciprocal Changes Distant from the Site of Spinal Osteotomies Affect Global Postoperative Alignment - Eric Klineberg; Frank Schwab; Christopher Ames; Richard Hostin; Shay Bess; Justin S. Smith; Munish C. Gupta; Oheneba Boachie; Robert A. Hart; Behrooz A. Akbarnia; Douglas C. Burton; Virginie Lafage (Advances in Orthopedics)
Introduction. Three-column vertebral resections are frequently applied to correct sagittal malalignment; their effects on distant unfused levels need to be understood. Methods. 134 consecutive adult PSO patients were included (29 thoracic, 105 lumbar). Radiographic analysis included pre- and postoperative regional curvatures and pelvic parameters, with paired independent t-tests to evaluate changes. Results. A thoracic osteotomy with limited fusion leads to a correction of the kyphosis and to a spontaneous decrease of the unfused lumbar lordosis (−8°). When the fusion was extended, the lumbar lordosis increased (+8°). A lumbar osteotomy with limited fusion leads to a correction of the lumbar lordosis and to a spontaneous increase of the unfused thoracic kyphosis (+13°). When the fusion was extended, the thoracic kyphosis increased by 6°. Conclusion. Data from this study suggest that lumbar and thoracic resection leads to reciprocal changes in unfused segments and requires consideration beyond focal corrections.